(E)-Methyl 3-(4-chlorophenyl)-2-{2-[(E)-(hydroxyimino)methyl]phenoxymethyl}acrylate - SakthiMurugesan, K. (International Union of Crystallography, 2011)
In the title compound, C(18)H(16)ClNO(4), the dihedral angle between the mean planes through the aromatic rings is 83.8 (8)°. The hydroxyethanimine group is essentially coplanar with the ring to which it is attached [O—N—C—C torsion angle = −177.96 (13)°]. The molecules are linked into centrosymmetric R (2) (2)(6) dimers via O—H⋯N hydrogen bonds. The crystal packing is further stabilized by C—H⋯O interactions.